Arctic ecosystems shaped mammalian dispersal and diversification before the Cretaceous–Paleogene mass extinction - Sarah L. Shelley; Jaelyn J. Eberle; Gregory M. Erickson; Patrick S. Druckenmiller (Proceedings of the National Academy of Sciences, 2026)
High-latitude terrestrial ecosystems are commonly viewed as marginal environments to deep-time evolutionary innovation, yet their role in shaping biotic dispersal, diversification, and survivorship remains poorly understood. The Upper Cretaceous Prince Creek Formation of northern Alaska (paleolatitude ~80–85°N) yields the most northerly known Mesozoic mammals and provides a rare opportunity to examine the ecological and biogeographic roles of polar terrestrial ecosystems. Here, we describe three multituberculate species, Camurodon borealis , Qayaqgruk peregrinus , and Kaniqsiqcosmodon polaris , and integrate comparative morphology with phylogenetic and biogeographic analyses to evaluate patterns and timing of dispersal and diversification across a high-latitude Asian–American terrestrial corridor. Qayaqgruk peregrinus is recovered within the Mongolian Djadochtatherioidea, representing the earliest direct evidence for multituberculate dispersal from Asia into North America. Kaniqsiqcosmodon polaris constitutes the oldest known member of the Microcosmodontidae, suggesting a high-latitude origin for a derived North American lineage that later diversified during the Paleocene following the Cretaceous–Paleogene mass extinction. Camurodon borealis represents the northernmost occurrence of the Cimolomyidae. Pronounced variation in dental morphology among the Prince Creek multituberculates indicates ecological differentiation and niche partitioning within an extreme, highly seasonal polar environment. Our findings indicate that Late Cretaceous Arctic ecosystems supported both sustained intercontinental exchanges as early as 91.82 Ma and endemism. Our results challenge interpretations of polar regions as evolutionary peripheries and instead identify them as important contributors to mammalian evolutionary dynamics prior to the Cretaceous–Paleogene mass extinction.